Предмет: Химия,
автор: Donrim
Fe-FeSO4-FeCl2-Fe(NO3)3-Fe (OH3)-Fe2O3
Ответы
Автор ответа:
0
Fe(NO3)3 → Fe(OH)3 → Fe2O3 → Fe → FeCl2
3NaOH + Fe(NO3)3 = 3NaNO3 + Fe(OH)3↓
2Fe(OH)3 = Fe2O3 + 3H2O
Fe2O3 + 3H2 = 2Fe + 3H2O
Fe + 2HCl= FeCl2 + H2↑
3NaOH + Fe(NO3)3 = 3NaNO3 + Fe(OH)3↓
2Fe(OH)3 = Fe2O3 + 3H2O
Fe2O3 + 3H2 = 2Fe + 3H2O
Fe + 2HCl= FeCl2 + H2↑
Похожие вопросы
Предмет: Другие предметы,
автор: Аноним
Предмет: Алгебра,
автор: karolinakoshkareva
Предмет: Математика,
автор: almazobeko
Предмет: Математика,
автор: rahim20015
Предмет: Математика,
автор: Fikus82